2017
DOI: 10.1371/journal.pone.0177288
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the transmission of risk for antisocial behavior problems across generations

Abstract: Previous studies have shown that children of alcohol use disorder (AUD) parents are more likely to develop alcohol problems as well as antisocial and other behavior problems. The purpose of this study was to examine gender discordance in the effect of early maternal and paternal influences on antisocial behaviors of boys and girls, as well as the environmental factors that moderate the parental effects. Specifically, we examined the effects of childhood and adulthood antisocial behavior of the parents on offsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
(52 reference statements)
1
5
0
2
Order By: Relevance
“…Furthermore, this study found that the intergenerational transmission of MD from mothers to offspring had a higher association than the one from fathers to offspring, as previous research suggested [ 50 53 ]. This fact could be related with both, social and biological factors.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, this study found that the intergenerational transmission of MD from mothers to offspring had a higher association than the one from fathers to offspring, as previous research suggested [ 50 53 ]. This fact could be related with both, social and biological factors.…”
Section: Discussionsupporting
confidence: 75%
“…Previous research indicates that for mothers, the association between parental and child psychopathology is specific, whereas for fathers it is non-specific: mothers' internalizing problems have been associated to child internalizing problems and the same applied for externalizing problems [49]. Furthermore, existing research, albeit limited, suggests that maternal intergenerational transmission of MD is particularly strong [49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Homel and Warren ( 2017 ) found that fathers’ binge drinking raised the risk of adolescent drinking by their daughters but not by their sons. Li et al ( 2017 ) identified influence from mothers’ alcohol use disorder to early adult anti-social behaviour by sons (but not by daughters). To our knowledge, cross-gender transmission of problem gambling has not been noted in previous literature but it has not in fact been actively looked for since most research combines male and female observations in the receiving generation, potentially masking gender-specific transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of antisocial behavior is heterogeneous, so that each condition is different from the other and the notion of the causes of antisocial behavior relies on different factors such as environmental, biological, and genetic factors [ 5 ]. Different biological factors have an implication in developing antisocial behavior, such as brain damage during pregnancy, brain hypoxia in the womb or birth, or neuropsychological dysfunction and psychosocial influences [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies also showed that environmental factors have a major role in the creation of antisocial behavior, especially during childhood [ 7 ]. Examples of such factors include; the person exposed to domestic violence and abused in his home, his parents being drug users, was abused during his childhood either sexually, physically, or emotionally or an unstable home environment [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%